Evaluation of Retinal Layers and Choroidal Structures Using Optical Coherence Tomography in Alopecia Areata - Burak OREN; Gozde AKSOY AYDEMIR; Serkan DUZAYAK; Hasan KIZILTOPRAK (Medeniyet Medical Journal)
Objective: To evaluate the macula, retinal nerve fiber layer (RNFL), retinal layers, and choroidal thickness (CT) using spectral domain optical coherence tomography (SD-OCT) in patients with alopecia areata (AA). Methods: The right eyes of 42 AA patients (17 women, 25 men) and 42 controls (18 women, 24 men) were included in the study. Each subject underwent thorough ophthalmic examination and SD-OCT (Heidelberg Engineering) measurements. Central macular thickness (CMT), RNFL, the average thicknesses of the ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OPL), outer nuclear layer (ONL), retinal pigment epithelium (RPE), inner retinal layers (IRL), photoreceptor layers (PRL) as well as subfoveal, temporal and nasal CT were measured. Results: In all sectors, no significant difference was observed between the AA group and the control group with regard to the mean values for CMT and RNFL (p>0.05, for all). There was not a significant difference between the AA group and the control group with regard to the thickness of the GCL, IPL, INL, OPL, ONL, RPE, IRL, and PRL (p>0.05 for all). CT at the subfoveal, temporal, and nasal regions was significantly thicker in the AA group than in the control group (p<0.05 for all). Conclusions: Along with T-lymphocyte-mediated hair follicle damage, choroidal melanocyte damage and inflammation can also be observed in AA patients. CT may increase secondary to melanocyte inflammation in AA patients.